Amphibian skin peptides: Diversity, biological functions, and research progress - Zihui Chen; Qing Pan; Jiaming Zhang; Ren Lai; Wenhua Yu; Aili Wang (Toxicon, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

Uniaxial compressive behavior of frozen silty clay at extreme low temperature with varying initial water content - Jiaming Xian; Wansheng Pei; Yuanming Lai; Mingyi Zhang; Fan Yu; Yanyan Chen (Cold Regions Science and Technology, 2026)

3D printing programmed diagnostic and therapeutic bioactive “all-in-one” microspheres with multistimuli responsiveness for cartilage regeneration - Feifei Zhou; Wenjing Zhang; Yuan Yang; Shuyu Liu; Jing Long; Siqi Zhang; Jiaming Cui; Yuxiao Lai; Weimin Zhu (Chemical Engineering Journal, 2025)

Anti-PD-L1 blockade facilitates antitumor effects of radiofrequency ablation by improving tumor immune microenvironment in hepatocellular carcinoma - Jiahua Liang; Mingjian Ma; Wei Feng; Qiongcong Xu; Dong Chen; Jiaming Lai; Jiancong Chen (Apoptosis, 2025)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

Ancient and modern mitogenomes of red deer reveal its evolutionary history in northern China - Bo Xiao; Tianjiao Wang; Adrian M. Lister; Junxia Yuan; Jiaming Hu; Shiwen Song; Haifeng Lin; Siren Wang; Chunxue Wang; Dong Wei; Xulong Lai; Xiumei Xing; et al. (Quaternary Science Reviews, 2023)

Effects of nitrogen addition on soil faunal abundance: A global meta‐analysis - Junxi Hu; Shixing Zhou; Liehua Tie; Xiong Liu; Xing Liu; Anjiu Zhao; Jiaming Lai; Lin Xiao; Chengming You; Congde Huang (Global Ecology and Biogeography, 2022)
Aim Soil fauna has a wide range of ecosystem functions. Anthropogenic atmospheric nitrogen (N) deposition affects the structure and function of soil fauna by changing the microenvironment and resources. Given that soil faunal responses can vary considerably among taxonomic groups, N deposition rate, and ecosystems, however, there is little consensus. We aimed to evaluate the effects of N deposition on different soil faunal taxa across different terrestrial ecosystems. Location Global. Time period 1970–2021. Major taxa studied Soil fauna. Methods We conducted a meta‐analysis that yielded 264 observations from 43 publications. We evaluated the responses to N addition of soil faunal abundance for three different taxa (nematodes, mites, collembolans) in three ecosystem types (cropland, forest, and grassland). Results Our results showed an overall negative effect of N addition on soil fauna. However, the effect varied among soil faunal taxa. Specifically, N addition had no significant effects on the abundance of collembolans and mites in any ecosystem. On the other hand, N addition significantly reduced the abundance of all nematode trophic groups except bacterivores. The overall reduction of soil fauna is likely driven by the nematode response. The negative effects of N addition on nematode abundance were contingent on the N addition rate, N addition form, and ecosystem type. N addition decreased nematode abundance at N addition rates of more than 100 kg/ha/year. Inorganic N addition negatively affected nematode abundance. Finally, N addition had a greater adverse effect on nematodes in cropland and grassland compared to forest ecosystems. Main conclusions Our results demonstrate the overall negative effects of N addition on nematode abundance. Excessive N addition should be avoided in cropland and grassland management. Further, we suggest the application of organic fertilizer instead of inorganic fertilizer to minimize the N‐induced negative effects on soil nematodes.